(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the compliance with pre-analytical procedures among nurses in clinical departments at Vung Tau General Hospital in 2025. Subjects and methods: A cross-sectional descriptive study using direct observation was conducted from October 2024 to November 2025. A total of 186 observations of 62 nurses across 11 clinical departments were included. A standardized checklist was used to assess compliance in blood collection, sample preservation, and transportation procedures. Results: Overall compliance was at a moderate level. Compliance rates were 70.97% for venous blood collection, 68.28% for sample preservation, and 56.99% for sample transportation. Lower compliance was mainly observed in transportation procedures and some technical steps in blood collection. Conclusion: Compliance with pre-analytical procedures among nurses at Vung Tau General Hospital was relatively good but inconsistent across steps, particularly in sample transportation. Strengthening supervision, training, and standardization is necessary to improve laboratory quality.